Child Maltreatment and the Child Welfare System as Environmental Factors in the International Classification of Functioning - Kim, Katherine; Moss, Corinne; Park, Jane Jungyoon; Wekerle, Christine (Frontiers in Rehabilitation Sciences, 2022)
The World Health Organization (WHO) defines child maltreatment as any form of neglect, exploitation, and physical, emotional, or sexual abuse, committed against children under the age of 18. Youth involved in the child welfare system report more maltreatment experiences and environmental turbulence (number of moves, caseworkers, etc.), placing them at greater risk for poorer physical and mental health. The International Classification of Functioning, Disability, and Health (ICF) provides a framework to describe health conditions and severity of disabilities for an individual and/or group in the context of environmental factors. The Maltreatment and Adolescent Pathways (MAP) study is a longitudinal study, assessing self-reports on variables (e.g., child maltreatment history, trauma symptoms, dating violence, substance use, etc.) of youth in an urban child protective services system. This paper focuses on 11 of the 24 MAP publications, which can be considered within the ICF framework. The purpose of this paper is to analyze these MAP studies, with maltreatment and involvement in the child welfare system as environmental factors that work in tandem with mental health problems and disabilities among child welfare-involved youth. Findings point to significant relationships across child maltreatment histories and contextual factors (i.e., trauma symptomatology, psychological distress, intellectual disabilities, child welfare status) and functioning impairments (i.e., substance use, adolescent dating violence, sleep problems, sexual risk-taking). Coping motives among child welfare-involved youth emerged as a significant impairment in the ICF framework, related to child maltreatment histories and trauma symptomatology. The interrelated nature of these factors in the MAP studies suggest the value of the ICF model, with a focus on environmental factors (e.g., child maltreatment histories and child welfare system involvement) in guiding service provision for foster care and/or maltreated youth.